(untitled) (Journal of Management & Business, 2021)
This article considers some theories and ways in which some modern scientists and economists have claimed that a “new economy” could emerge, the shift from manufacturing to services, technological transformation and flexible labor markets or telecommuting. The advantages and disadvantages of economic change, its benefits and costs, are discussed as people desperately try to balance the pressing demands of work and personal life in times of crisis.